Attitudes of Gifted Children to People with Disabilities - Urbanovská, Eva; Hanáková, Adéla; Horváthová, Ivana; Kučera, Pavel; Kunhartová, Monika; Pastieriková, Lucia; Regec, Vojtech; Stejskalová, Kateřina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Talent is characterized as asynchronous development, which combines accelerated cognitive abilities and increased intensity to create inner experiences and awareness that are different from their quality standards. Article reflects the results of research that aimed to describe the group of exceptionally gifted children aged in terms of their attitudes, opinions and concerns to people with disabilities. To obtain the data was specifically chosen method of focus groups and projective technique unfinished sentences. Target groups were presented unfinished sentences, so that on the basis of the replies received gave to identify topics that are relevant to it. One of the objectives was to find out the answers obtained from the opinions and attitudes towards the phenomenon of disability - to obtain information to enable understanding of the way in which this target group thinks about people with disabilities.